Job Rotation and Competence on Employee Performance Mediated by Motivation among Civil Servant Educational Staff at UPN “Veteran” Yogyakarta - Kesworo, Pawoko Uji; Subyantoro, Arief; Hikmah, Khoirul (Cita konsultindo, 2025)
This study examines the influence of job rotation and competence on employee performance, with motivation as a mediating variable among civil servant educational staff at Universitas Pembangunan Nasional “Veteran” Yogyakarta. Using a quantitative explanatory approach, data were collected from 83 respondents through an online questionnaire. The findings show that job rotation positively affects employee performance, indicating that structured rotation helps employees adapt and enhance productivity. Competence also has a positive and significant effect on performance, suggesting that higher skills and professional abilities lead to better results. Furthermore, motivation mediates the relationship between job rotation, competence, and employee performance. The study concludes that effective job rotation and continuous competence development can enhance motivation and improve performance among educational staff. Organizations should therefore focus on empowering employees through skill development and work enrichment to achieve higher institutional performance.